(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the tradition of writing risala (Arabic letters), focusing on the structure, linguistic features, and communicative functions of the administrative letter (risala idariyya). The study analyzes the differences between official and personal correspondence, the relationship between sender and recipient, and stylistic requirements in Arabic formal writing. The results show that logical organization, objectivity, and etiquette formulas are essential elements of official communication. The paper also provides pedagogical recommendations for teaching Arabic formal writing in academic contexts.